Validation of the Turkish Version of the Sarcoidosis Health Questionnaire: A cross-sectional study: Turkish Version of the Sarcoidosis Health Questionnaire - Kavas, Murat; Kaymaz, Serdar; Aydoğan Eroglu, Selma; Karasu, Ugur; Cobankara, Veli; Boga, Sibel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Objective and aim: Sarcoidosis, a multisystemic granulomatous disease, generally results in a lower quality of life (QoL) because of its unexpected course and diverse clinical symptoms. The Sarcoidosis Health Questionnaire (SHQ) evaluates the QoL for people with sarcoidosis in terms of their health. This study set out to validate the SHQ in a group of Turkish sarcoidosis patients. Methods: The study included a total of 146 adult sarcoidosis patients (63 male and 83 female; mean age, 44±3.6 years; range, 27-63 years) between May 2019 and September 2021. Preparation, forward translation, reconciliation, back translation/back translation review, harmonization, finalization, and proofreading comprised the steps of the testing procedure for translation and cultural adaptation. The participants filled out three questionnaires, including the SHQ, 36-Item Short Form (SF-36) Health Survey, and King’s Sarcoidosis Questionnaire (KSQ), and underwent pulmonary function tests (PFTs). Results: Of the patients, 95% had lung involvement, with a mean number of 1.3 organs involved. Each SHQ component displayed a moderate to high internal consistency, ranging from 0.806 to 0.844. The whole scale’s Cronbach’s alpha value was 0.781. The SHQ total score significantly correlated with physical component summary (p< 0.001, r=0.360) and mental component summary (p<0.001, r=0.352) scores of SF-36, and the general health status (p< 0.001, r=0.478), medication component (p<0.001, r=0.456), and eye component scores of KSQ (p<0.001, r=0.545). When patients were divided into groups based on organ involvement (p=0.01), oral steroid medication (p<0.001), and types of symptoms (P=0.021), there were significant differences in the total SHQ scores. Conclusion: The Turkish version of SHQ can be a valid and accurate instrument for assessing the health of sarcoidosis patients in Turkey. When combined with normal physiological, radiological, and serological examinations, SHQ can assess the QoL of sarcoidosis patients and give useful new information.